Scissors, Paper, Rock : A Novel - Johnson, Fenton (Kentucky voices., 2016)
Along with his siblings, Raphael Hardin left his childhood home in rural Kentucky. Grappling with an AIDS diagnosis, he returns to care for his dying father. Told from the perspectives of Raphael, his family, and their lifelong neighbor, Fenton Johnson's landmark novel reveals the blood struggles and binding loves of a broken family made whole.